The road to circularity: a framework for and experiences in collecting road data in a circular renovation process - Bram Entrop (Acta Polytechnica CTU Proceedings)
The construction and transport sectors both have a substantial impact on the environment. The construction, maintaining and renovating of roads involves both these sectors and the environmental impact of this work can be reduced. The basic principle of a circular economy is to close material loops and so retain the highest utility, quality and value of products, components and materials as possible. An important question in this respect is how to qualify and quantify material flows. Material and project passports seem to be part of the solution to improve insights and sharing information on quantities and qualities of materials used in construction projects. This paper has used a literature study on material passports and has taken into account current project management software used by a municipality, in order to share a framework for organising and collecting road construction data. Furthermore, various scanning equipment and procedures were employed onsite in an experiment in collecting actual road data. This resulted in a large amount of different data files that have been interpreted and incorporated into the existing database structure of the municipality. The insights gained may help other researchers, principals and contractors in the road construction industry in collecting and storing reliable data necessary to renovate roads circularly.